The Relationship between the Psoas Muscle Mass Index and Postoperative Complications in Crohn's Disease: A Retrospective Cohort Study - Maho Sasaki; Tatsunari Fukuoka; Masatsune Shibutani; Hiroaki Kasashima; Kiyoshi Maeda (Journal of the Anus, Rectum and Colon)
Objectives: Sarcopenia is generally defined based on the age-related muscle mass and weakness. However, it has been reported that patients with Crohn's disease, who develop severe inflammation of the gastrointestinal tract, are more likely to develop sarcopenia. We retrospectively investigated the effect of the iliopsoas muscle area, which is an indicator of sarcopenia, on postoperative complications in patients with Crohn's disease. Methods: We included 98 patients with Crohn's disease who underwent surgery in our department between January 2016 and December 2021, and performed retrospectively analyzed. The psoas muscle index (PMI) was calculated as the average of the left and right iliopsoas muscles (L3, cm2) / height2. We divided patients into the low PMI (men <2.33 cm2/m2, women <1.85 cm2/m2) and normal PMI groups and compared their preoperative and intraoperative factors and postoperative outcomes. Results: The median age of the 98 patients was 37.0 (17-77) years. Complications were noted in 40 patients (40.8%), including 10 (10.2%) with anastomotic leakage. There were 26 (26.5%) patients with a low PMI. The incidence of all postoperative complications, grade 2 complications, anastomotic leakage and surgical site infection (SSI) were significantly higher in the low-PMI group than in the normal-PMI group. According to a multivariate analysis, low PMI (p=0.04) was only independent predictor for grade 2 or above postoperative complications. Conclusions: A low PMI is associated with postoperative complications, especially anastomotic leakage, in patients with Crohn's disease.